Flexural Strength of Translucent Zirconia Materials Produced with Different Multilayer Technologies: An In Vitro Study - Fahad Bakitian (International Journal of Dentistry)
Objective. To evaluate the flexural strength of two translucent multilayered zirconia materials produced with different multilayer technologies. Methodology. Eighty bar-shaped zirconia specimens were prepared from two different multilayered zirconia materials (IPS e.max® ZirCAD Prime and KATANA™ Multilayered Zirconia HTML) and divided into eight groups (n = 10) based on the materials used and the individual layers of the disc for each material: Dentin Prime, Transition Prime, Translucent Prime, Multilayered Prime, Dentin HTML, Transition HTML, Translucent HTML, and Multilayered HTML. The bar-shaped zirconia specimens were cut to include all the layers from translucent to dentin In Multilayered Prime and Multilayered HTML groups. All specimens were fully sintered after cutting from multilayered zirconia discs and subjected to three-point flexural strength test using the universal testing machine. Results. The specimens made of HTML zirconia material showed significantly (P<0.001) higher flexural strength than those made of IPS e.max® ZirCAD Prime material, with no significant difference (P>0.05) compared to the specimens in the Dentin Prime group. The Dentin Prime specimens had the highest flexural strength (743 ± 116 MPa) compared to those in the Translucent Prime (514 ± 120 MPa), Transition Prime (575 ± 102 MPa), and Multilayered Prime (531 ± 132 MPa) groups. The flexural strength of the specimens from the individual layers of HTML zirconia material was not significantly different (P>0.05) among the Dentin HTML (763 ± 56 MPa), Translucent HTML (791 ± 106 MPa), Transition HTML (816 ± 85 MPa), and Multilayered HTML (793 ± 102 MPa) groups. Conclusion. Multilayered zirconia materials produced with different yttria contents by layer have lower flexural strength than those produced with gradient shade technology and the same yttria content for each layer. Therefore, various factors such as the type of prostheses, nesting strategies of prostheses within the zirconia disc, and the desired aesthetical requirements should be considered when selecting the multilayered zirconia materials.